2013
DOI: 10.1289/ehp.1205963
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Expression in Response to Controlled Exposure to Diesel Exhaust: Attenuation by the Antioxidant N -Acetylcysteine in a Randomized Crossover Study

Abstract: Background: Adverse health effects associated with diesel exhaust (DE) are thought to be mediated in part by oxidative stress, but the detailed mechanisms are largely unknown. MicroRNAs (miRNAs) regulate gene expression post-transcriptionally and may respond to exposures such as DE.Objectives: We profiled peripheral blood cellular miRNAs in participants with mild asthma who were exposed to controlled DE with and without antioxidant supplementation.Methods: Thirteen participants with asthma underwent controlled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(56 citation statements)
references
References 52 publications
1
54
0
Order By: Relevance
“…Dysregulation of miRNA expression has been implicated in diverse diseases, including inflammatory lung disease [Oglesby et al, 2010], cardiovascular disease [Small et al, 2010], and cancer [Melo and Esteller, 2011;Chen et al, 2012]. In recent years, an increasing body of literature has reported dysregulated miRNA expression profiles resulting from direct exposures to various environmental pollutants, including metal-rich particulate matter [Bollati et al, 2010], diesel exhaust particles [Jardim et al, 2009;Yamamoto et al, 2013], and tobacco smoke [Izzotti et al, 2009;Schembri et al, 2009]. Among these studies, metal-rich particulate matter and diesel exhaust particle exposures were reported to aggravate systemic oxidative stress and to up-regulate expression of miRNAs, particularly of miR-21 [Bollati et al, 2010;Yamamoto et al, 2013]; whereas cigarette smoke exposures, both in vitro with human primary bronchial epithelial cells [Schembri et al, 2009] and in vivo with rat lungs [Izzotti et al, 2009], down-regulate expression of miRNAs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dysregulation of miRNA expression has been implicated in diverse diseases, including inflammatory lung disease [Oglesby et al, 2010], cardiovascular disease [Small et al, 2010], and cancer [Melo and Esteller, 2011;Chen et al, 2012]. In recent years, an increasing body of literature has reported dysregulated miRNA expression profiles resulting from direct exposures to various environmental pollutants, including metal-rich particulate matter [Bollati et al, 2010], diesel exhaust particles [Jardim et al, 2009;Yamamoto et al, 2013], and tobacco smoke [Izzotti et al, 2009;Schembri et al, 2009]. Among these studies, metal-rich particulate matter and diesel exhaust particle exposures were reported to aggravate systemic oxidative stress and to up-regulate expression of miRNAs, particularly of miR-21 [Bollati et al, 2010;Yamamoto et al, 2013]; whereas cigarette smoke exposures, both in vitro with human primary bronchial epithelial cells [Schembri et al, 2009] and in vivo with rat lungs [Izzotti et al, 2009], down-regulate expression of miRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, an increasing body of literature has reported dysregulated miRNA expression profiles resulting from direct exposures to various environmental pollutants, including metal-rich particulate matter [Bollati et al, 2010], diesel exhaust particles [Jardim et al, 2009;Yamamoto et al, 2013], and tobacco smoke [Izzotti et al, 2009;Schembri et al, 2009]. Among these studies, metal-rich particulate matter and diesel exhaust particle exposures were reported to aggravate systemic oxidative stress and to up-regulate expression of miRNAs, particularly of miR-21 [Bollati et al, 2010;Yamamoto et al, 2013]; whereas cigarette smoke exposures, both in vitro with human primary bronchial epithelial cells [Schembri et al, 2009] and in vivo with rat lungs [Izzotti et al, 2009], down-regulate expression of miRNAs. Although those dysregulated miRNA expression profiles were clearly detectable immediately after exposures to the environmental pollutants ended, whether the influence of the pollutants on miRNA expression is retained long after the exposures end has not yet been adequately investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Although many studies have showed relationships between environmental chemicals and miRNAs, most of them were conducted via in vitro tests (Jardim et al, 2009), and few focused on examining miRNA expression related to chemicals on human, especially genotoxic chemicals (Bollati et al, 2010;Yamamoto et al, 2013). Here, we screened miRNAs sensitive to Cr(VI) exposure, and validated their target genes related to genetic damage using bioinformatic methods and ELISA.…”
Section: Discussionmentioning
confidence: 99%
“…One and two way ANOVAs coupled to the Holm-Sidak test for multiple comparisons were performed using SigmaPlot v11 and STATISTICA v7 in order to find statistical differences in aromatase relative expression levels (P<0.05). Normalized data (log 2) were plotted according to Yamamoto et al, (2013).…”
Section: Discussionmentioning
confidence: 99%